Effect of 1-MCP Treatment on Quality and Reactive Oxygen Metabolism of Prune Fruits During Storage Period - Kaiyue BI; Ainiyangur AIZHEBA; Ziyue HAI; Liya SU; Yuhan WU; Mengying ZHANG; Xuewen LI (Shipin gongye ke-ji, 2025)
To investigate the preservation effect of 1-methylcyclopropene (1-MCP) treatment on prune plums, 'France' prune plums from Kashi Jiashi County, Xinjiang, were used as the test material. The fruits were fumigated with different concentrations of 1-MCP (0, 0.05, 0.15, and 0.3 μL/L) for 24 hours and then stored in a cold storage at (−1~1) ℃ for 90 days. The results indicated that all concentrations of 1-MCP effectively inhibited the decline in storage quality of the prune plums, delayed the reduction in fruit firmness and decay rate, maintained the content of soluble solids and titratable acidity, postponed the respiratory peak, and reduced the respiratory intensity. Among them, 0.30 μL/L 1-MCP treatment showed the best effect. Further research demonstrated that 1-MCP could effectively inhibit the increase in cell membrane permeability and malondialdehyde content of prune plums, and enhance the activities of superoxide dismutase, catalase, peroxidase, and ascorbate peroxidase. These results suggested that 1-MCP could delay fruit quality deterioration, reduce fruit respiration rate, enhance the activity of antioxidant enzymes in prune plums, postpone the increase in hydrogen peroxide content, and decrease the generation rate of superoxide anions, thereby maintaining the storage quality of prune plums for a certain period of storage.